Finnikin of the rock - Marchetta, Melina, 1965- (Somerville, Mass. : Candlewick Press, 2010)
Now on the cusp of manhood, Finnikin, who was a child when the royal family of Lumatere was brutally murdered and replaced by an imposter, reluctantly joins forces with an enigmatic young novice and fellow-exile, who claims that her dark dreams will lead them to a surviving royal child and a way to regain the throne of Lumatere.
Maps on endpapers.
Pub Weekly
Pub Weekly, January 2010
Young Adult.
Young Adult
Keywords: Good and evil -- Juvenile fiction; Monarchy -- Juvenile fiction; Fantasy; Good and evil -- Fiction; Monarchy -- Fiction; Good and evil -- Fiction; Monarchy -- Fiction; Fantastic fiction; Fantastic fiction